1994
DOI: 10.1152/ajprenal.1994.266.5.f756
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction sequentially induces new urea transport processes in rat initial IMCD

Abstract: We reported that feeding rats 8% protein for 4 wk induces two new urea transport processes in initial inner medullary collecting ducts (IMCD); neither is present in rats fed 18% protein. In this study, we measured the time course of induction of these transporters in perfused initial IMCD segments from rats fed 8% protein. Net urea flux was induced after 3 wk, whereas vasopressin-stimulated passive urea permeability (P(urea)) was induced after 2 wk. 8-Bromoadenosine 3',5'-cyclic monophosphate (8-BrcAMP) signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 0 publications
5
57
1
Order By: Relevance
“…Changes in renal urea N reabsorption in relation to the N content of the diet were consistent with existing reports (Tebot et al, 1998;Marini et al, 2004); renal tubular load of urea N increased, whereas the proportion of urea N reabsorbed decreased, with increasing dietary N. Schmidt-Nielsen et al (1958) reported that urea reabsorption rose when animals were fed low N diets, and Isozaki et al (1994) characterized the involvement of the kidney in this phenomenon in rats.…”
Section: Urinary Creatinine Excretion Plasma Urea N Concentration Rsupporting
confidence: 89%
“…Changes in renal urea N reabsorption in relation to the N content of the diet were consistent with existing reports (Tebot et al, 1998;Marini et al, 2004); renal tubular load of urea N increased, whereas the proportion of urea N reabsorbed decreased, with increasing dietary N. Schmidt-Nielsen et al (1958) reported that urea reabsorption rose when animals were fed low N diets, and Isozaki et al (1994) characterized the involvement of the kidney in this phenomenon in rats.…”
Section: Urinary Creatinine Excretion Plasma Urea N Concentration Rsupporting
confidence: 89%
“…Schmidt-Nielsen and colleagues first demonstrated the existence of active urea reabsorption which is coupled to sodium reabsorption in the kidney of the spiny dogfish, Squalus acanthias (16). We showed that urea is actively reabsorbed via a secondary active, sodium-coupled cotransport process in the rat initial IMCD (IMCD 1 ) from rats fed a low-protein diet for 3 wk (9)(10)(11). We also showed that urea is actively secreted via a secondary active, sodium-coupled countertransport process in the deepest portion of the rat terminal IMCD, the IMCD 3 , but not in the middle third of the IMCD, the IMCD 2 , nor in the initial IMCD of rats fed a normal diet (12).…”
Section: Introductionmentioning
confidence: 94%
“…In addition to facilitated urea transport, there is evidence for active urea transport process(es) in the kidney of rat (9)(10)(11)(12), rabbit (13), dog (14,15), spiny dogfish (16), and human (17). Schmidt-Nielsen and colleagues first demonstrated the existence of active urea reabsorption which is coupled to sodium reabsorption in the kidney of the spiny dogfish, Squalus acanthias (16).…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen the closer characterisation of a family of aquaporins, which have the general property of moving water and urea across membranes. The identi®ca-tion of a urea transporter in the kidney of the rat which is responsive to dietary protein intake (Isozaki et al, 1994;Smith et al, 1995), the demonstration of a transporter which is speci®cally located in the renal collecting duct and the colon (You et al, 1993), and the ®nding of similar capabilities in the human colon (Ritzhaupt et al, 1998) opens the opportunity for a co-ordinated response. It is possible that on a low-protein diet, enhanced retention of urea in the kidney is matched by an enhanced capacity to move urea into the colon where the nitrogen can be salvaged through bacterial activity.…”
Section: Urea Water and The Kidneymentioning
confidence: 99%